Tri-Focal Configuration of Three-Dimensional Metallic Waveguide-Array Lens Antennas of Rotman Lens Concept for Multi-Beam Applications - Hsi-Tseng Chou; Zong-Chen Tsai; Siddhartha Panigrahi (IEEE Access, 2019)
This paper presents a design methodology of three-dimensional (3-D) passive metallic waveguide-array lens antenna (MWALA) by implementing the Rotman lens concept (RLC) for collinear multi-beam radiations on the same angular plane. The RLC methodology extends the original concept of two-dimensional (2-D) tri-focal Rotman lens into a 3-D one in free space. Thus, the MWALA has a planar aperture facing to the radiation boresight to resemble a planar phased array of waveguide antennas and also has a curved focal surface profile (CFSP) on the opposite side to receive the illumination by the radiations of feed antennas. The three co-planar focal points are specified to define a circular focal arc (CFA) for multiple feed placement to radiate multi-beams through this MWALA. The boundary formed by the CFSP and CFA resembles the shape of Rotman lens equivalently realized in free space. In addition, the shortage of freedoms in conventional MWALA design limited to dual-focus configurations and resulting in narrow scan angles, is relaxed by adopting the phase velocities inside the waveguides as an additional freedom to realize a tri-focal configuration and broaden the scan angles of multi-beam radiation. Theoretical foundation and design guidelines are summarized with numerical and experimental examples presented to validate the feasibility.